Modulation of eddy kinetic energy, temperature variance, and eddy heat fluxes by surface buoyancy forcing - Munday, D; Zhai, X (2013)
Although mesoscale eddies are a ubiquitous feature of the world's oceans, mechanisms determining their strength and variability remain poorly understood. Here we investigate the effects of surface buoyancy forcing on eddy kinetic energy (EKE), temperature variance, and lateral eddy heat fluxes. In keeping with previous investigations, sustained heat loss ultimately leads to an increase in the magnitude of EKE, whereas sustained heat gain only alters the spatial pattern of EKE, albeit enhancing the temperature variance. These changes to the eddy field and stratification are shown to result in changes in meridional eddy heat flux and residual meridional overturning circulation, which acts to bring the system to equilibrium with the applied surface buoyancy forcing. © 2012 Elsevier Ltd.